Tarbiyah Al-Aulad Fi Al-Islam Perspektif Abdullah Nashih Ulwan - Niken Ristianah (Intizam, Jurnal Manajemen Pendidikan Islam, 2017)
Child education is actually a part of individual education which in the religion of Islam seeks to prepare and shape it to become a useful member of society and people who pray in life. Even children's education (if directed well) is basically a solid foundation in preparing righteous individuals who are ready to assume responsibility and the burden of life. Children are a mandate for their parents. his holy heart is a valuable substance. If he is accustomed to goodness, then he will grow in goodness. Anyone if he is accustomed to ugliness and ignored like an animal, then he will be miserable and miserable. Therefore, guarding children is by educating, disciplining, and teaching them noble characters. Family as the first place for children to have social relations. If a child experiences problems in development, then the family is appointed as the person responsible for the child's problem.